Infrared Imaging Does Not Predict the Presence of Malignancy in Patients with Suspicious Radiologic Breast Abnormalities. Issue 4 (26th May 2014) - Collett, Abigail E.; Guilfoyle, Caramarie; Gracely, Edward J.; Frazier, Thomas G.; Barrio, Andrea V.
Abstract The NoTouch BreastScan (NTBS) is a non‐invasive infrared imaging device which measures thermal gradients in breasts using dual infrared cameras and computer analysis. We evaluated NTBS as a predictor of breast cancer in patients undergoing minimally invasive biopsy. In this IRB‐approved prospective trial, 121 female patients underwent NTBS prior to scheduled tissue biopsy. Twenty‐two patients were excluded due to uninterpretable scans (n = 18), diagnosis of a nonprimary breast malignancy (n = 1), or no biopsy performed (n = 3) for a total of 99 patients. Five patients had bilateral breast biopsies and one patient had two ipsilateral biopsies, resulting in 105 biopsies. Patients were prospectively scanned using a high specificity mode, termed NTBS1. All 99 patients were retrospectively re‐evaluated in a high sensitivity mode, NTBS2. Of 105 biopsies performed in 99 women, 33 (31.4%) were malignant and 72 (68.6%) were benign. NTBS1 demonstrated a sensitivity of 45.5% and a specificity of 88.9%. Of 94 normal contralateral breasts, 9.6% had a positive NTBS1. In the retrospective evaluation, NTBS2 demonstrated a sensitivity of 78.8% and a specificity of 48.6%. Half (50%) of the normal contralateral breasts had a positive NTBS2. NTBS does not accurately predict malignancy in women with suspicious imaging abnormalities. The higher sensitivity mode results in an unacceptable number of false positives, precluding its use. Infrared imaging did not improve the sensitivity or specificity of mammography in this clinical setting.